Visible Out-of-plane Polarized Luminescence and Electronic Resonance in Black Phosphorus - Schué, Léonard; Goudreault, Félix A; Righi, Ariete; Resende, Geovani C; Lefebvre, Valérie; Godbout, Émile; Tie, Monique; Ribeiro, Henrique B; Heinz, Tony F; Pimenta, Marcos A; Côté, Michel; Francœur, Sébastien; et al. (Nano letters, 2022)
Black phosphorus (BP) is unique among layered materials because of its homonuclear lattice and strong structural anisotropy. While recent investigations on few-layer BP have extensively explored the in-plane (a, c) anisotropy, much less attention has been given to the out-of-plane direction (b). Here, the optical response from bulk BP is probed using polarization-resolved photoluminescence (PL), photoluminescence excitation (PLE), and resonant Raman scattering along the zigzag, out-of-plane, and armchair directions. An unexpected b-polarized luminescence emission is detected in the visible, far above the fundamental gap. PLE indicates that this emission is generated through b-polarized excitation at 2.3 eV. The same electronic resonance is observed in resonant Raman with the enhancement of the Ag phonon modes scattering efficiency. These experimental results are fully consistent with DFT calculations of the permittivity tensor elements and demonstrate the remarkable extent to which the anisotropy influences the optical properties and carrier dynamics in black phosphorus.